First principles studies of multidimensional hybrid materials - Yin, Jun (2017)
Multidimensional hybrid systems play a major role in most applications of modern materials science, including relevant research areas of energy conversion and storage (solar cells, batteries), chemical and biochemical processes (photocatalysis, drug delivery, sensors), nanoelectronics (LEOs, FETs), and nanophotonics (light sources and amplifiers, plasmonic waveguides and modulators). By taking advantage of two or more components with distinctly different physical and electronic properties, for instance organic and inorganic constituents, hybridization at the atomic level and exploitation of dimensionality effects allow designing nanostructured material with properties "on demand". From the theoretical standpoint, the in-depth understanding of structure-property relationships of such inhomogeneous systems poses new challenges: methods that proved successful for describing homogeneous components may not be applicable to the hybrid systems, and are likely to fail to capture the physics of abrupt heterointerfaces. In this thesis, we consolidated a theoretical framework to study hybrid nanostructured materials by a combination of computational strategies and first-principle approaches, including density functional theory (OFT), time-dependent OFT and many-body perturbation theory. Within this framework, we studied the structural, vibrational, electronic and photophysical properties of model material systems with different dimensionality and functions, including polymer/fullerene blends, polymer/Ill-V heterointerfaces, organic-inorganic perovskites for photovoltaic applications, and metallic/dielectric topological insulators for active plasmonics. Our main findings are the following: i) a complete description of the vibrational fingerprints of polaronic and excitonic states m conjugated polymers; ii) the quantification of dimensionality and surface polarity effects on charge transfer and separation in hybrid polymerllll-V (film and quantum dots) photovoltaic systems; iii) the demonstration of dimensionality and self-trapping effects on charge transport and photoluminescence of multidimensional organic-inorganic perovskites for photovoltaic and light-emission applications; iv) the determination of composition-dependent dielectric and metallic optical properties of topological insulator crystals for low-loss plasmonic devices operating in the visible part of the spectrum. Our predictions compare favorably with structural and spectroscopic data of the actual hybrid material systems, demonstrating the flexibility and potential of first principle calculations for the computational discovery of novel material systems, and their optimization for real-life applications.